PENGARUH KEBERAGAMAN TENAGA KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (PT. PARKLAND WORLD INDONESIA PLANT 2) - Suhendri Suhendri (LPPM Universitas Banten jaya, 2020)
ABSTRACT This research aims to know the workforce diversity and work environment together and partially on the performance of the employees of PT. Parkland World Indonesia Plant 2. This study provides an overview of the extent to which the effect of workforce diversity and work environment on employee performance. The objects in this study were 53 employees of PT. Parkland World Indonesia Plant 2. The research method uses simple linear regression analysis method to conduct data analysis. The results of the study simultaneously, the diversity of the workforce and work environment affect the work performance of employees. The diversity of the workforce in this study has a positive and significant effect on employee performance. The work environment in this study has a positive and significant effect on employee performance. It is known that workforce diversity and work environment are important factors in order to improve employee performance at this Parkland World Indonesia Plant 2 company. For this reason, management needs to increase the diversity of the workforce of its employees and to improve a positive work environment for its employees in improving employee performance